Bombing and the Two Vietnams - Vu Vuong; Simon Chang; Michael Palmer (Institute of Labor Economics (IZA), 2021)
The Vietnam War occurred when Vietnam was divided into two states with contrasting institutions. North Vietnam was characterized by a command economy under a stable political regime, whereas South Vietnam experienced a market economy and prolonged political instability. This paper uses this context to investigate the heterogeneous effect of childhood bombing exposure on health in adulthood. On average we found negative long-term effects on adult height and body mass index among the South Vietnamese population, while their counterparts in the North were barely affected. We argue that this heterogeneity is most likely attributable to the interplay of institutions and bombing.
Keywords: I15; O15; I31; H56; N35; N45; 330; bombing; body mass index; institutions; nutrition transition; Vietnam